Suriname : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1995)
This report analyzes economic developments in Suriname during the 1990s. In 1990-92, real GDP recovered moderately, but inflation accelerated, reaching 58 percent in the 12 months ended December 1992, owing to a further weakening of financial policies. Interest rates became sharply negative in real terms, which initiated a gradual shift out of domestic financial assets. The external accounts remained weak, and the overall balance of payments showed deficits that were financed by a decline in international reserves and an accumulation of external payments arrears.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet